Plant growth promoting bacteria as an alternative strategy for salt tolerance in plants: A review - Numan, Muhammad; Bashir, Samina; Khan, Yasmin; Mumtaz, Roqayya; Shinwari, Zabta Khan; Khan, Abdul Latif; Khan, Ajmal; AL-Harrasi, Ahmed (Microbiological research, 2018)
[Display omitted] Approximately 5.2 billion hectare agriculture land are affected by erosion, salinity and soil degradation. Salinity stress has significantly affecting the fertile lands, and therefore possesses a huge impact on the agriculture and economy of a country. Salt stress has severe effects on the growth and development of plants as well as reducing its yield. Plants are inherently equipped with stress tolerance ability to responds the specific type of stress. Plants retained specific mechanisms for salt stress mitigation, such as hormonal stimulation, ion exchange, antioxidant enzymes and activation of signaling cascades on their metabolic and genetic frontiers that sooth the stressed condition. Additional to the plant inherent mechanisms, certain plant growth promoting bacteria (PGPB) also have specialized mechanism that play key role for salt stress tolerance and plant growth promotion. These bacteria triggers plants to produce different plant growth hormones like auxin, cytokinine and gibberellin as well as volatile organic compounds. These bacteria also produces growth regulators like siderophore, which fix nitrogen, solubilize organic and inorganic phosphate. Considering the importance of PGPB in compensation of salt tolerance in plants, the present study has reviewed the different aspect and mechanism of bacteria that play key role in promoting plants growth and yield. It can be concluded that PGPB can be used as a cost effective and economical tool for salinity tolerance and growth promotion in plants.